2020
DOI: 10.1093/biolinnean/blz196
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled ontogeny of in vivo bite force and mandible morphology reveals effects of weaning and sexual maturation in mice

Abstract: The link between performance, morphology and their sources of variation is a major target of evolutionary functional biology. In vertebrates, many studies have linked in vivo bite force to skull morphology, mostly at the interspecific level. Within species, however, the ontogeny of bite force, in relation to the development of the mandible, remains poorly known, despite its relevance for life history and for the co-evolution of form and function. Here, ontogenetic trajectories of bite force, correlated with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Growth in cranial size is often found to be the primary way to increase bite force across ontogeny (La Croix et al ., 2011b; Santana and Miller, 2016; Law et al ., 2016b; Ginot et al ., 2020). However, many carnivorans also exhibit significant cranial shape changes across ontogeny such as the development of the sagittal and nuchal crests (Tanner et al ., 2010; La Croix et al ., 2011a; Tarnawski et al ., 2013; Tarnawski et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Growth in cranial size is often found to be the primary way to increase bite force across ontogeny (La Croix et al ., 2011b; Santana and Miller, 2016; Law et al ., 2016b; Ginot et al ., 2020). However, many carnivorans also exhibit significant cranial shape changes across ontogeny such as the development of the sagittal and nuchal crests (Tanner et al ., 2010; La Croix et al ., 2011a; Tarnawski et al ., 2013; Tarnawski et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the mandible of the mouse undergoes major changes from the first stage (7–14 days). Indeed, it has already been shown that the bite force of mouse juveniles increases well before food weaning [55], which may explain early bone remodelling [56]. Early competition among pups and lower parental care in mice [10,57,58] may explain this acceleration of shape development and the correlated functional changes in mice compared with the two other species.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding system must change from the sucking movement to active chewing in only a few days. In mice, bite force increases drastically in the days preceding weaning (Ginot et al, 2020). In the Hystricomorpha species, parental care is different, with long behavioural weaning and less brutal dietary weaning, over a much longer period (Wolff & Sherman, 2008).…”
Section: Evolution Of Postnatal Trajectoriesmentioning
confidence: 99%